ENHANCING ENGLISH PROFICIENCY THROUGH INTERACTIVE LEARNING - Marsela, Anis; Lubis, Iqrom Nur Fadhil; Aziz, Abdul (International Journal of Community Service in Language, Literature, Culture, and Their Teaching, 2025)
This study explores the implementation of a Fieldwork Practice (PKL) program for children in care, focusing on enhancing their English language proficiency through innovative teaching methods. The program addressed challenges such as varying proficiency levels, engagement difficulties, and limited technological resources by incorporating tailored materials, gamification, and technology-driven learning. Through interactive activities like storytelling, role-playing, and online quizzes, children in care demonstrated significant improvements in vocabulary, listening, and speaking skills. Additionally, community-building initiatives fostered a supportive learning environment. The results indicate that adaptive methodologies and interactive approaches effectively enhance language acquisition and children in care engagement, offering insights for future educational programs in similar settings.